Patrimônio urbano: o persistente desencontro entre a teoria e a prática observado nas ações do Programa Monumenta - Azevedo, Maria Helena de Andrade (2022)
Since the end of the 18th century, several guidelines on how to intervene in heritage have been propagated based on the work of preservation theorists, and, in the 20th century, also through heritage charters – international documents with recommendations to be respected when intervening. From those analytical perspectives, the emergence and consolidation of restoration is situated as a specific disciplinary field that will dedicate itself to proposing, intervening, monitoring and questioning actions related to architectural and urban structures of different historical moments. Those theories have been guided by concerns on valuation, deterioration, restoration techniques, respect for heritage, cooperation and heritage education, thus consolidating the existence of a theoretical framework. When observing cultural heritage preservation programs carried out through governmental actions in contemporary Brazil such as Monumenta Program (1995-2010) that financed urban interventions in many Brazilian cities, it can be seen that urban heritage has also been target of actions, differently from times when only historical monuments were considered. Currently, that urban heritage is part of cultural consumption which has led interventions to seek plastic-formal proposals that enable new uses, sometimes causing the reinvention of traditions. Taking such reality into account, this doctoral thesis questions how preservationist recommendations and also those of the heritage charts have been interpreted by the Monumenta Program. Therefore, it is essential, on the one hand, to understand the concept of Urban Heritage according to authors such as John Ruskin, Alöis Riegl, Gustavo Giovannoni, Françoise Choay or Jukka Jokilehto and, on the other, the birth of Urbanism as a disciplinary field, due to urban problems brought about by events like the Industrial Revolution. The thesis also addresses the trajectory of heritage preservation in Brazil since the creation of IPHAN, and discusses physical interventions carried out in three open public places: the Théberge Open, in Icó, CE; São Pedro Square, in Mariana, MG; and São Francisco Square, in São Cristóvão, SE. From a methodological point of view, the evidences here examined have been documents prepared by the Government, such as the Monumenta Program Project itself, intervention projects, petitions, manuals, meeting reports, events proceedings, seminars, lectures and recommendations provided by both the inspection agencies and the technical staff from the Project Execution Units. The squares were studied from a historical and morphological point of view. As for the reading of the projects and the resulting works, various procedures were adopted, such as photographic survey, discussion of the applicable regulations, description of the physical space and project analysis. Semi-structured interviews were also carried out with the architects responsible for the proposals. At the end of the research, it was found that the Monumenta Program did not adopt the references of conservation theory so as to guide its actions.